The Effect of Etanol Vapor on Quality and Shelf Life of Cauliflower (Brassica oleraceavar. botrytis) in a Room Temperature - Martini, Ni Ketut Sari; Utama, I Made Supartha; Pudja, Ida Ayu Rina Pratiwi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The purpose of this research was to determine the effect of ethanol vapor and to find the best treatment concentration to maintain quality and extend the shelf life of cauliflower. The research used a completely randomized design (CRD) with five levels of ethanol concentration: 0%, 5%, 10%, 15%, and 20%. Cauliflower florets without ethanol vapor treatment were used as the control and stored at room temperature. The parameters measured were respiration rate, weight loss, color, vitamin C content, total dissolved solids, organoleptic properties (including color, smell, and freshness), and intensity of damage. The results showed that the 10% ethanol concentration was the best treatment, as it reduced respiration rate and weight loss, maintained color, suppressed the decrease in vitamin C content, achieved the best organoleptic scores for color, smell, and freshness, and reduced the intensity of damage in cauliflower.